Solve for \( u \). \[ 8(u-1)=6 u-6 \] Simplify your answer as much as possible. \( u=\square \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
First, let's distribute the 8 on the left side of the equation: \[ 8(u - 1) = 8u - 8 \] Now, we can rewrite the equation as: \[ 8u - 8 = 6u - 6 \] Next, we will move all terms involving \( u \) to one side and constant terms to the other side. Subtract \( 6u \) from both sides: \[ 8u - 6u - 8 = -6 \] This simplifies to: \[ 2u - 8 = -6 \] Now, add 8 to both sides to isolate the term with \( u \): \[ 2u = -6 + 8 \] This simplifies to: \[ 2u = 2 \] Finally, divide both sides by 2 to solve for \( u \): \[ u = 1 \] So, \( u = 1 \).